Kemampuan Pemecahan Masalah Matematika Materi Pola Bilangan Ditinjau dari Tingkat Kepercayaan Diri Siswa - Ghurfah, Ahliah; Sripatmi, Sripatmi; Novitasari, Dwi; Baidowi, Baidowi (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2023)
The purposes of this research were to describe mathematical problem-solving ability on number pattern materials based on the level of self-confidence of 8th-grade students at MTsN 3 Mataram in the academic year 2022/2023. This research is descriptive qualitative research. The research subjects consisted of 6 students who were taken using a purposive sampling technique. As for the data collection techniques, this research is using three methods, which are questionnaires, tests, and interviews. The data analysis technique uses Miles and Huberman consisting of data reduction, data display, and conclusions are drawn. The results show that subjects with high self-confidence and moderate self-confidence are able to carry out the stages of understanding the problem, the stages of devising a plan, the stages of carrying out the plan, and the stages of looking back. Meanwhile, subjects with low self-confidence are only able to carry out the stages of understanding the problem.